2023
DOI: 10.5755/j01.erem.79.3.33123
|View full text |Cite
|
Sign up to set email alerts
|

Species Composition and Carbon Stock of Rehabilitated Mangrove Forest in Kupang District, East Nusa Tenggara, Indonesia

Jeriels Matatula,
Pandu Yudha Adi Putra Wirabuana,
Emad Hassan Elawad Yasin
et al.

Abstract: Since 1994, the community around the mangrove forest in Kupang district, East Nusa Tenggara Province, Indonesia, has rehabilitated the mangrove forest. Unfortunately, almost three decades of the success story of mangrove rehabilitation has not followed appropriate documentation on biodiversity and potential carbon stock. This research aimed to describe the species composition and estimate the carbon stock of rehabilitated mangrove forests. Forty-five sampling plots were distributed using purposive sampling bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Mangrove species capable of thriving and adjusting to rising sea levels should therefore be protected (Ward et al 2016). Matatula et al (2023), also observed a limited range of species in mangrove forests following ten years of restoration efforts in the Kupang Gulf. The occurrence may arise due to the distinctive attributes of this ecosystem, which serve as inhibitory factors for species.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Mangrove species capable of thriving and adjusting to rising sea levels should therefore be protected (Ward et al 2016). Matatula et al (2023), also observed a limited range of species in mangrove forests following ten years of restoration efforts in the Kupang Gulf. The occurrence may arise due to the distinctive attributes of this ecosystem, which serve as inhibitory factors for species.…”
Section: Discussionmentioning
confidence: 95%
“…Three indicators were selected to evaluate plant-animal diversity metrics in every site, i.e., richness, heterogeneity, and evenness. Species richness was quantified using the Margalef index (𝐷 𝑚𝑔 ), while species heterogeneity was assessed using the Shannon-Wienner index (𝐻 ′ ) (Matatula et al 2023). On the other hand, the species evenness was determined using the Pielou-Evenness index (𝐽 ′ ) (Suyanto et al 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mangrove forests play a significant role in their physical, biological, and economic contributions (Supandi et al, 2023;Matatula et al, 2023). They generate an annual ecosystem service value of around 21,100 USD.hectares -1 (Getzner and Islam, 2020;Sari et al, 2023).…”
Section: Introductionmentioning
confidence: 99%